Polarization-Singular Approach to Imaging Mueller-Matrix Polarimetry in the Differential Diagnosis of Histological Sections of Biopsy of Tumors of the Uterus and Prostate - Dubolazov, A.; Ushenko, V.; Trifonyuk, L.; Stashkevich, A.; Soltys, I.; Ushenko, Y.; Tomka, Y.; Ushenko, A.; Gantyuk, V.; Gorodensky, P. (Frontiers in Physics, 2021)
The possibilities of the diagnostic use of the singular approach in the Mueller-matrix polarimetry of biological tissues are considered. Within the framework of the phase anisotropy model, the relationships between the polarization-singular states of the biological tissue image and the characteristic values of its Mueller-matrix images are determined. A technique is proposed for measuring the distributions of the number of characteristic values of the elements of the Mueller matrix, which determine the mechanisms for the formation of S and C states is proposed. It was found that the statistical analysis of the distributions of the number of characteristic values of the elements of the Mueller matrix of biological tissues is effective for differentiating the polarization properties of such objects associated with pathological changes in the orientational structure of birefringent fibrillar networks. Within the framework of statistical analysis, the effectiveness of differential diagnosis of the pathological state of myometrial tissue has been demonstrated.